Penerapan Model Pembelajaran Numbered Head Together dalam Pembelajaran IPS Kelas VIII SMP Negeri 11 Lubuklinggau - Jeni Haryanti; Supriyanto; Agus Susilo (CV. Creative Tugu Pena, 2024)
This research aims to determine the completeness of social studies learning outcomes for class VIII students at SMP Negeri 11 Lubuklinggau after implementing the Numbered Head Together learning model. The research approach used in this research is quantitative descriptive, with an experimental research type. The research design in this study was one group pretest-posttest. The data collection technique was carried out using a test technique in the form of multiple choice with a total of 40 questions. The data analysis technique in this research is a quantitative technique. The population in the study were all class VIII students with a total of 132 students. The sampling technique used in this research was a simple random sampling technique with the samples taken in this research in class VIII.3 with a total of 33 students. Based on the analysis results from hypothesis testing with the t test, it is known that tcount 5.175 with a significance level of 5% at degrees of freedom dk = N-1 = 33-1= 32. Thus tcount (5.175) > ttable (1.697) for a significance level of 5 %, this means Ho is rejected and Ha is accepted. In other words, the hypothesis proposed in the research can be accepted as true, so it can be concluded that the social studies learning outcomes of class VIII students at SMP Negeri 11 Lubuklinggau after implementing the Numbered Head Together (NHT) learning model are significantly complete